The effect of knockdown of insulin receptor substrates 1 and 2 on glucose and lipid metabolism in human hepatoblastoma cells - Yu, Tianfei; Li, Ming; Dong, Huiying; Xie, Pengyu; Sun, Wanzhu; Meng, Bo; Mu, Yanshuang (Archives of Biological Sciences, 2018)
Paper description: Hepatic insulin signaling mediated by insulin receptor substrates 1 and 2 plays a central role in the development of type 2 diabetes mellitus. Our results show that knockdown of IRS-1 and IRS-2 results in PEPCK upregulation. Decreased IRS-1 was associated with a decrease in glucokinase expression. Knockdown of IRS-2 resulted in upregulation of lipogenic enzymes, SREBP-1c and Cyp7a1. Dual-knockdown of IRS-1 and IRS-2 was associated with defective Akt kinase activation. Our results suggest that hepatic IRS-1 and IRS-2 play divergent roles in gene signaling pathways and have complementary roles hepatic metabolism control. Abstract: Hepatic insulin signaling mediated by insulin receptor substrates 1 and 2 (IRS-1 and IRS-2, respectively) plays a central role in the development of type 2 diabetes mellitus. Although the functions of individual components in the signaling network have been extensively studied, our knowledge is still limited with regard to how the signals are integrated and coordinated in the complex network to render their functional roles. To investigate the specific functions of IRS-1 and IRS-2 in regulating liver function in humans, we developed a vector-mediated RNA interference (RNAi) technique in which short hairpin RNAs were used to knock down IRS-1, IRS-2, or both, by 50-60%, in cultured human hepatoblastoma (HepG2) cells. The knockdown of IRS-1 and IRS-2 resulted in upregulation of the gluconeogenic enzyme phosphoenolpyruvate carboxykinase (PEPCK). Decreased IRS-1 was also associated with a decrease in glucokinase (GCK) expression, whereas the knockdown of IRS-2 resulted in the upregulation of lipogenic enzymes, sterol regulatory element-binding protein 1c (SREBP-1c) and cholesterol 7 alpha-hydroxylase (Cyp7a1). Dual-knockdown of IRS-1 and IRS-2 in HepG2 cells was associated with defective GTPase α serine/threonine-protein kinase (Akt) activation. Taken together, our results demonstrate that hepatic IRS-1 and IRS-2 play divergent roles in gene-signaling pathways and have complementary roles in the control of hepatic metabolism. https://doi.org/10.2298/ABS180705040Y Received: July 5, 2018; Revised: September 15, 2018; Accepted: September 17, 2018; Published online: September 20, 2018 How to cite this article: Yu T, Li M, Dong H, Xie P, Sun W, Meng B, Mu Y. The effect of knockdown of insulin receptor substrates1 and 2 on glucose and lipid metabolism in human hepatoblastoma cells. Arch Biol Sci. 2018;70(4):757-64.